1. Let the four consecutive numbers be x, x+1, x+2, x+3
The sum of four consecutive number is already given to us = 70
Therefore
⇒(x)+(x+1)+(x+2)+(x+3)=70
We need to combine x as we have four x terms in the equation. The next step is to get all of the x’s on one side of the equation and all the numbers on the other side. The same rule applies – whatever you do to one side of the equation, you must do to the other side as well!
⇒4x+6=70⇒4x=64⇒x=16
So, the four numbers are 16, 17, 18 and 19.
Hence, the greatest number among them is 19.
Answer:
12.5%
Step-by-step explanation:
There are two types of spinners here and the outcome of them is independent. That means
P(odd number,C) = P(odd number) * P(C)
There are two odd numbers out of four numbers in the first spinner. The chance of odd number will be:
P(odd) = 2/(2+2)= 1/2= 50%
There are four letters and the desired outcome is C. The chance for C will be:
P(C)= 1/4= 25%
Then the chance will be:
P(odd number,C) = P(odd number) * P(C)
P(odd number,C) =50% * 25% = 12.5%
Answer:
with waht
Step-by-step explanation:
Answer:
the answer is c :)
Step-by-step explanation:
<u>Question 8</u>
a^2 + 7a + 12
= (a+3)(a+4)
When factorising a quadratic, the product of the two factors should equal the constant term (12), and the sum of the two factors should equal the linear term (7). To find the two factors, list out the factors of 12 (1x12, 2x6, 3x4) and identify the pair that adds up to 7 (3+4).
An alternative method if you get stuck during your exam would be to solve it algebraically using the quadratic formula and then write it in the factorised form.
a = (-7 +or- sqrt(7^2 - 4(1)(12)) / 2(1)
= (-7 +or- sqrt(1))/2
= -3 or -4
These factors are the negative of the values that would go in the brackets when written in factorised form, as when a = -3 the factor (a+3) would equal 0. (If it were positive 3 instead, then in the factorised form it would be a-3).
<u>Question 10</u>
-3(x - y)/9 + (4x - 7y)/2 - (x + y)/18
Rewrite each fraction with a common denominator so you can combine the fractions into one.
= -6(x - y)/18 + 9(4x - 7y)/18 - (x + y)/18
= (-6(x - y) + 9(4x - 7y) - (x + y)) /18
Expand the brackets and collect like terms.
= (-6x + 6y + 36x - 63y - x - y)/18
= (29x - 58y)/18
= 29/18 x - 29/9 y